BLOOD PRESSURE AND HEMODYNAMIC PARAMETERS AFTER ACUTE AEROBIC, RESISTANCE AND COMBINED EXERCISES IN RESISTANT HYPERTENSIVE SUBJECTS. (June 2018) - Vilella, N. Fraccari Pires; Gasparetti, C.; Bavaresco, B.; Júnior, H. Coelho; Pioli, M. Rodrigues; Santos, V.F.; Almeida, A.; Corrêa, N. Batista; Brunelli, V.; De Faria, A.P.; Modolo, R.; Rodrigues, B.; et al.
Abstract : Objective: Evaluate the acute effects of aerobic, resistance and combined exercise on blood pressure (BP) and hemodynamic parameters in resistant (RH) and non-resistant (non-RH) hypertensive subjects Design and method: This interventional, randomized, single-blind, crossover study was conducted with 20 patients (RH = 10, non-RH = 10) from the Resistant Hypertension Clinic at UNICAMP- Brazil. All subjects were submitted to a previous adaptation of physical activity to determine the load to be implemented in resistant exercise session. Subjects were randomized to perform 45 minutes of: a) Aerobic exercise (AE): activity on a treadmill (70% of maximum heart rate obtained from ergometric test); b) resistance exercise (RE): 4 series of 12 repetitions of each exercises at moderate intensity (Borg scale); and c) combined exercise (CE): AE (25 minutes) + RE (20 minutes). Clinical and hemodynamic parameters were assessed before and after each exercise session. Results: We found no difference between RH and non-RH subjects after each exercise, except for a reduction in aortic pulse pressure (41 ± 13 vs. 37 ± 9 mmHg, p = 0, 04) after CE in non-RH subjects and Augmentation Index after AE (31 ± 11 vs. 22 ± 9 %, p = 0, 02) in RHTN patients. Daytime 24 hour ambulatory diastolic pressure (76 ± 8 vs. 74 ± 8 mmHg, p < 0, 001) and nighttime pulse pressure (58 ± 11 vs. 43 ± 8 mmHg, p = 0, 03) decreased in RH subjects after CE. When we compared the type of exercise in RH subjects, we found a higher reduction on systolic (AE −7 ± 26 vs. RE +8 ± 25 vs. CE −15 ± 21 mmHg, p < 0.001), diastolic (AE −5 ± 14 vs. RE +2 ± 15 vs. CE −8 ± 10 mmHg, p = 0, 04) and mean blood pressure levels (AE −4 ± 17 vs. RE +7 ± 17 vs. CE −8 ± 13 mmHg, p = 0, 002) after CE Conclusions: The hemodynamic parameters after one session of AE, RE and CE were similar between RH and non-RH subjects. However, when compared the different types of exercises, we observed that EC was more effective in reducing blood pressure in RH patients.